2022
DOI: 10.1038/s41598-022-18565-2
|View full text |Cite
|
Sign up to set email alerts
|

Age as a primary driver of the gut microbial composition and function in wild harbor seals

Abstract: Dietary changes are the major variation cause in the composition of the gut microbiota. The short lactation phase in phocids provides an exceptional opportunity to explore the microbiota's response to a quick transition from a milk-based to a solid diet. We investigated the effects of age and sex on the gut microbiota of harbor seals in Mexico using rectal and fecal samples from pups and adults. 16S gene sequencing revealed age explains most of the observed variations in microbial composition. Individuals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 73 publications
0
9
1
Order By: Relevance
“…While many of the Gammaproteobacteria results at the genus level lacked fine‐scale taxonomic resolution, the genus Anaerobiospirillum did appear in the Santa Rosa Island fox versus skunk comparison. This genus has been previously isolated from the gut microbiomes of harbor seal pups ( Phoca vitulina ; Pacheco‐Sandoval et al., 2022 ) and rural coyotes ( Canis latrans ; Sugden et al., 2020 ) with protein‐rich diets. These associations may again reflect a combination of evolutionary history and contemporary foraging ecology, as island fox diets likely contain food items sourced from marine and terrestrial habitats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many of the Gammaproteobacteria results at the genus level lacked fine‐scale taxonomic resolution, the genus Anaerobiospirillum did appear in the Santa Rosa Island fox versus skunk comparison. This genus has been previously isolated from the gut microbiomes of harbor seal pups ( Phoca vitulina ; Pacheco‐Sandoval et al., 2022 ) and rural coyotes ( Canis latrans ; Sugden et al., 2020 ) with protein‐rich diets. These associations may again reflect a combination of evolutionary history and contemporary foraging ecology, as island fox diets likely contain food items sourced from marine and terrestrial habitats.…”
Section: Discussionmentioning
confidence: 99%
“…been previously isolated from the gut microbiomes of harbor seal pups(Phoca vitulina;Pacheco-Sandoval et al, 2022) and rural coyotes (Canis latrans;Sugden et al, 2020) with protein-rich diets. These associations may again reflect a combination of evolutionary history and contemporary foraging ecology, as island fox diets likely contain food items sourced from marine and terrestrial habitats.…”
mentioning
confidence: 99%
“…For this, we identified the bacterial genera and ASVs that were present in >85% of samples at mean relative abundances of at least 0.5%. This prevalence cutoff was an intermediate of the cutoffs that have been previously employed in other mammalian microbiome studies (80% prevalence cutoff for harbor seals and 9 species of nonhuman primates, 90% prevalence cutoff for wild baboons, 100% prevalence cutoff for domestic cats and Welsh ponies) ( 119 123 ). For ASVs for which genus was unknown, the next most refined level of known taxonomic classification was used (e.g., family).…”
Section: Methodsmentioning
confidence: 99%
“…Due to expected biological differences [ 17 , 29 ], all analyses were performed separately for pups and weaners.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Northern elephant seals ( Mirounga angustirostris ) show sexual dimorphism in their gut microbiome even before external physical differences between males and females are visible [ 7 ]. However, for harbour seals, a study found minimal sex-related gut microbiome differences in wild harbour seal pups and adults in Mexico [ 17 ], while a more recent study in harbour seal neonates under rehabilitation in California found sexual dimorphism evidence in their gut microbiome [ 18 ]. In addition to the factors mentioned, Stoffel and colleagues [ 7 ] found that healthy elephant seal pups have a higher microbiome alpha diversity than clinically impaired animals.…”
Section: Introductionmentioning
confidence: 99%